Magnetic flux flows of optical quasi binormal magnetic flows with flux density - Körpınar, Talat; Körpınar, Zeliha; Demirkol, Rıdvan Cem (Taylor and Francis Ltd., 2021)
In this paper, we extract distinctive determination for quasi magnetic flux of the quasi binormal magnetic flows of magnetic quasi (Formula presented.) -particle by considering directional frame in 3D ordinary space. Also, we construct some advanced optical qualifications for magnetic quasi Lorentz flux for magnetic quasi- (Formula presented.) particle along with the quasi directional frame fields. Then, we calculate quasi magnetic Lorentz flux with directional-quasi magnetic fields. Besides, we obtain original simulations with regard to directional potentials for directional-quasi magnetic binormal flows with Heisenberg optical ferromagnetic model. Magnetic optical flux surfaces are demonstrated in a homogeneous optical flux surface by fractional numerical and applied developments. By using above models, we get new fractional model with q-homotopy analysis transform method (qHATM) and its illustrative presentation to consider magnetic optical flux surface. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 02.40.-k; 03.50.De; 04.20.-q; flux density; Heisenberg ferromagnetic spin; Laplace transform (LT); q-Homotopy analysis transform method; quasi binormal magnetic flows; Quasi directional frame